Contributions to the functional morphology of caudate skulls: kinetic and akinetic forms - Nikolay Natchev; Stephan Handschuh; Simeon Lukanov; Nikolay Tzankov; Borislav Naumov; Ingmar Werneburg (PeerJ, 2016)
A strongly ossified and rigid skull roof, which prevents parietal kinesis, has been reported for the adults of all amphibian clades. Our μ-CT investigations revealed that the Buresch’s newt (Triturus ivanbureschi) possess a peculiar cranial construction. In addition to the typical amphibian pleurokinetic articulation between skull roof and palatoquadrate associated structures, we found flexible connections between nasals and frontals (prokinesis), vomer and parasphenoid (palatokinesis), and between frontals and parietals (mesokinesis). This is the first description of mesokinesis in urodelans. The construction of the skull in the Buresch’s newts also indicates the presence of an articulation between parietals and the exocipitals, discussed as a possible kind of metakinesis. The specific combination of pleuro-, pro-, meso-, palato-, and metakinetic skull articulations indicate to a new kind of kinetic systems unknown for urodelans to this date. We discuss the possible neotenic origin of the skull kinesis and pose the hypothesis that the kinesis in T. ivanbureschi increases the efficiency of fast jaw closure. For that, we compared the construction of the skull in T. ivanbureschi to the akinetic skull of the Common fire salamander Salamandra salamandra. We hypothesize that the design of the skull in the purely terrestrial living salamander shows a similar degree of intracranial mobility. However, this mobility is permitted by elasticity of some bones and not by true articulation between them. We comment on the possible relation between the skull construction and the form of prey shaking mechanism that the species apply to immobilize their victims.